Total transcatheter correction of scimitar variant having dual pulmonary venous drainage - Arvind Sahadev Singh; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2020)
Scimitar syndrome is a clinical triad of anomalous pulmonary venous drainage, lung hypoplasia, and anomalous aortic blood supply to the lung segment. When there is dual pulmonary venous drainage both to inferior vena cava and left atrium, it is called scimitar variant. A young child presenting with recurrent chest infections, dextroposition of the heart, and scimitar shadow on chest X-ray was identified to have scimitar variant after a detailed evaluation and managed successfully by catheter interventions. This report discusses the embryogenesis and angiographic findings of scimitar variants, indications for interventions, and issues in its management.